PENERAPAN COVER LAGU OLEH RAINYCH RAN DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG PADA MAHASISWA TINGKAT I - Yola Feronika; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was conducted to determine the implementation of song media as learning Japanese vocabulary in hiragana letters for college students in class 2022. The type of research used was qualitative with an analytical descriptive method. Sources of data in this study were taken using purposive sampling by taking 27 college students to participate in learning using song media. The results in this study indicate that song media can be used as an alternative media and variations in the classroom to achieve learning objectives that can help college students to improve new Japanese vocabulary contained in song lyrics in a fun way.Keywords: Cover song, learning , Japanese vocabulary